"Consent is Good, Joyous, Sexy": A banner campaign to market consent to college students. Issue 8 (16th November 2016) - Thomas, Kristie A.; Sorenson, Susan B.; Joshi, Manisha
ABSTRACT: Objective : This study assessed the recall of, reaction to, and understanding of a brief campus banner campaign promoting consent in sexual relationships, and determined whether campaign exposure was associated with subsequent engagement in activities related to sexual assault education, awareness, and prevention.Participants : A stratified random sample of 1, 200 undergraduates was recruited during fall of 2010; 628 (52.3%) participated.Methods : To account for history and maturation, an experimental research design was employed with an online survey.Results : Direct and indirect campaign exposure was associated with increased action. Students expressed primarily positive reactions to and appeared to understand the consent message. The campaign appealed to and was associated with increased activity among a wide range of students with one exception: a negative effect was observed for business students.Conclusions : Colorful banners with pithy, upbeat messages hold promise for engaging undergraduates in conversations and proactive activities related to sexual assault prevention.